Electrolyte and lithium ion battery
By optimizing the proportion of lithium salt, film-forming agent and wetting agent in the lithium-ion battery electrolyte, and reducing the impedance of the electrolyte, the problem of rising battery cell temperature and serious side reactions in the fast charging process of lithium-ion batteries is solved, and the problem of increased battery cell temperature and serious side reactions is improved. The battery cycle stability and safety are achieved.
Patent Information
- Application Number
- CN202411561528.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-11
AI Technical Summary
The impedance of existing lithium-ion battery electrolytes is high, resulting in a higher temperature rise in the battery cell during fast charging, which is serious side effects, which is not conducive to fast charging performance.
It provides an electrolyte containing 10% to 18% lithium salt, 0.5% to 10% film forming agent, 0.05% to 5% wetting agent and residual solvent. By optimizing component ratio and structural design, it reduces the Impedance of the electrolyte.
By optimizing the components and proportions of the electrolyte, the impedance of the electrolyte is reduced, and the cycle stability and safety of lithium-ion batteries under fast charging conditions are improved.
Smart Images

Figure CN119419356A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an electrolyte and a lithium ion battery. Background Art
[0002] With the rapid development of the new energy industry in modern society, the high capacity and long battery life of commonly used batteries have been achieved. At the same time, people have put forward higher and higher requirements for charging speed. Due to the shortcomings of low intrinsic electronic conductivity and ion diffusion coefficient of lithium iron phosphate, its fast charging performance has always been inferior to that of ternary lithium batteries. The design of lithium iron phosphate materials can be optimized by structural nano-sizing, in-situ carbon coating, ion doping or crystal plane orientation engineering, and by optimizing the electrolyte dynamics, fast charging performance can be achieved in the iron-lithium system. During the fast charging process of the battery, due to the large current, the cell pole piece, diaphragm, electrolyte, etc. have impedance, resulting in a high temperature rise of the cell and serious side reactions, which is not conducive to fast charging performance. Therefore, it is urgent to develop an electrolyte with low impedance. Summary of the invention
[0003] The main purpose of the present invention is to provide an electrolyte and a lithium ion battery to solve the problem of high impedance of the electrolyte in the prior art.
[0004] In order to achieve the above object, according to one aspect of the present invention, an electrolyte is provided, which comprises, by mass percentage: 10% to 18% of lithium salt; 0.5% to 10% of film-forming agent; 0.05% to 5% of wetting agent; and the remainder of solvent; the structural formula of the wetting agent is: wherein R1 to R6 are independently selected from sulfonate, hydrogen, halogen, substituted or unsubstituted C1 to C 10 Alkyl, substituted or unsubstituted C1~C 10 Alkoxy, substituted or unsubstituted C3~C 10 Cycloalkyl, substituted or unsubstituted C2~C 10 Alkenyl, substituted or unsubstituted C2~C 10 Any one of alkynyl groups, and at least one substituent among R1 to R6 is a halogen or sulfonate group.
[0005] Furthermore, the above R1~R6 are each independently selected from any one of sulfonate group, hydrogen, halogen, substituted or unsubstituted C1~C6 alkyl, substituted or unsubstituted C1~C6 alkoxy, substituted or unsubstituted C3~C6 cycloalkyl, substituted or unsubstituted C2~C6 alkenyl, substituted or unsubstituted C2~C6 alkynyl; and / or, the sulfonate group is selected from any one of lithium sulfonate group, sodium sulfonate group, and potassium sulfonate group.
[0006] Further, the above-mentioned wetting agent is selected from any one or more of fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, 1,3,5-trifluorobenzene, 4-methylbenzenesulfonate lithium, sodium p-methylbenzenesulfonate, sodium styrenesulfonate, sodium isopropylbenzenesulfonate, potassium p-toluenesulfonate, potassium p-styrenesulfonate, lithium p-styrenesulfonate, potassium P-fluorobenzenesulfonic acid, lithium p-ethylbenzenesulfonate and sodium pentafluorobenzenesulfonate; preferably, the wetting agent is a combination of 1,3,5-trifluorobenzene and 4-methylbenzenesulfonate lithium, and the mass ratio of 1,3,5-trifluorobenzene to 4-methylbenzenesulfonate is 1:2 to 2.5, and the total mass content of 1,3,5-trifluorobenzene and 4-methylbenzenesulfonate lithium in the electrolyte is 0.8 to 3.5%.
[0007] Furthermore, the above-mentioned solvent includes a carboxylate solvent; the mass content of the carboxylate solvent in the electrolyte is 5% to 40%; preferably, the mass ratio of the carboxylate solvent to the wetting agent is 10 to 200:1; preferably, the carboxylate solvent is a short-chain linear carboxylate solvent; preferably, the structural formula of the short-chain linear carboxylate solvent is:
[0008] Among them, R7 and R8 are each independently selected from any one of hydrogen, halogen, substituted or unsubstituted C1~C3 alkyl, substituted or unsubstituted C2~C4 alkenyl, substituted or unsubstituted C2~C4 alkynyl, substituted or unsubstituted C1~C4 alkoxy, substituted or unsubstituted C2~C4 alkenyloxy, and substituted or unsubstituted C2~C4 alkynyloxy; preferably, the substituents in R7 and R8 are halogen.
[0009] Furthermore, the short-chain linear carboxylic acid ester solvent is ethyl acetate and / or ethyl difluoroacetate.
[0010] Further, the above-mentioned solvent also includes other solvents, and the other solvents are selected from any one or more of carbonate solvents, cyclic carboxylate solvents, sulfate solvents, sulfite solvents, anhydride solvents, phosphate solvents, phosphite solvents, amide solvents, nitrile solvents, sulfone solvents and ether solvents; preferably, the other solvent is selected from any one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, γ-butyrolactone, propionic anhydride, N-methylformamide, N-methylacetamide, acetonitrile, sulfolane, dimethyl sulfoxide, ethylene sulfite, propylene sulfite, triethyl phosphate, methyl ethyl phosphite, methyl sulfide, diethyl sulfite, dimethyl sulfite, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, fluorine-containing cyclic organic esters and sulfur-containing cyclic organic esters.
[0011] Furthermore, the other solvent is a combination of ethylene carbonate and dimethyl carbonate, and the mass ratio of ethylene carbonate to dimethyl carbonate is 2:7 to 3:1.
[0012] Further, the above-mentioned film-forming agent is selected from any one or more of vinylene carbonate, fluoroethylene carbonate, ethylene carbonate, difluoroethylene carbonate, 1,3-propyl sulfonate, 1,3-propylene sultone, vinyl sulfite, vinyl sulfate, methylene disulfonate, tris(trimethylsilyl)phosphate, 1,2,3-tris(2-cyano)propane, adiponitrile and succinonitrile; preferably, the film-forming agent is selected from any one or more of vinylene carbonate, fluoroethylene carbonate and tris(trimethylsilyl)phosphate; further preferably, the film-forming agent is a combination of vinylene carbonate, fluoroethylene carbonate and tris(trimethylsilyl)phosphate, and the mass ratio of vinylene carbonate, fluoroethylene carbonate and tris(trimethylsilyl)phosphate is 1:4:0.8 to 4:1:1.
[0013] Furthermore, the lithium salt is selected from any one or more of lithium hexafluorophosphate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate, lithium tetrafluorooxalatophosphate, lithium difluorobis(oxalatophosphate), lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(pentafluoroethylsulfonyl)imide and tris(trifluoromethylsulfonyl)methyllithium.
[0014] According to another aspect of the present invention, a lithium-ion battery is provided, comprising a positive electrode sheet, an electrolyte and a negative electrode sheet, wherein the electrolyte is the aforementioned electrolyte solution.
[0015] Applying the technical solution of the present application, the appropriate addition of lithium salt in the present application helps to improve the transmission efficiency of lithium ions. The appropriate addition of film-forming agent helps to form a stable SEI film on the surface of the positive and negative electrodes. The presence of SEI film helps to protect the electrode material from corrosion by the electrolyte, thereby helping to reduce the occurrence of side reactions, especially under high temperature or high rate charge and discharge conditions. The continuously repaired SEI film can effectively inhibit further reaction between the interface and the electrolyte, thereby helping to improve the cycle stability and safety of the battery. The addition of wetting agent helps to reduce the surface tension of the electrolyte, thereby facilitating the rapid penetration of the electrolyte in the electrode and the diaphragm, especially at high rate charge and discharge, which helps to reduce the desolvation energy of lithium ions on the electrode surface and reduce lithium deposition and dendrite formation. The wetting agent of the present application is an additive of a benzene structure. By introducing a halogen or sulfonate group on the benzene ring, it helps to achieve the hydrophilic and lipophilic properties of the wetting agent, and acts as a surfactant component in the electrolyte. The main structure of benzene is lipophilic, and the substituent is hydrophilic, which helps to rapidly reduce the surface tension of the electrolyte and improve the wetting effect of the electrolyte in the positive and negative electrodes and the diaphragm, thereby helping to reduce concentration polarization during the fast charge cycle. It is preferred to control the mass fractions of lithium salts, film formers, and wetting agents within the above range, which helps to further reduce the impedance of the electrolyte, thereby helping to improve the cycle stability of lithium-ion batteries under fast charge conditions. DETAILED DESCRIPTION
[0016] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0017] As analyzed in the background technology of the present application, the prior art has the problem of high impedance of the electrolyte. In order to solve this problem, the present application provides an electrolyte and a lithium-ion battery.
[0018] In a typical embodiment of the present application, an electrolyte is provided, which includes, by mass percentage: 10% to 18% lithium salt; 0.5% to 10% film-forming agent; 0.05% to 5% wetting agent; and the remaining solvent; the structure of the wetting agent is R1 to R6 are each independently selected from sulfonate, hydrogen, halogen, substituted or unsubstituted C1 to C 10 Alkyl, substituted or unsubstituted C1~C 10 Alkoxy, substituted or unsubstituted C3~C 10 Cycloalkyl, substituted or unsubstituted C2~C 10 Alkenyl, substituted or unsubstituted C2~C 10 Any one of alkynyl groups, and at least one substituent among R1 to R6 is a halogen or sulfonate group.
[0019] The appropriate addition of lithium salt in this application helps to improve the transmission efficiency of lithium ions. The appropriate addition of film-forming agent helps to form a stable SEI film on the surface of the positive and negative electrodes. The presence of SEI film helps to protect the electrode material from corrosion by the electrolyte, thereby helping to reduce the occurrence of side reactions, especially under high temperature or high rate charge and discharge conditions. The continuously repaired SEI film can effectively inhibit further reaction between the interface and the electrolyte, thereby helping to improve the cycle stability and safety of the battery. The addition of wetting agent helps to reduce the surface tension of the electrolyte, thereby facilitating the rapid penetration of the electrolyte in the electrode and the diaphragm, especially at high rate charge and discharge, which helps to reduce the desolvation energy of lithium ions on the electrode surface and reduce lithium deposition and dendrite formation. The wetting agent of the present application is an additive of a benzene structure. By introducing a halogen or sulfonate group on the benzene ring, it helps to achieve the hydrophilic and lipophilic properties of the wetting agent, and acts as a surfactant component in the electrolyte. The main structure of benzene is lipophilic, and the substituent is hydrophilic, which helps to rapidly reduce the surface tension of the electrolyte and improve the wetting effect of the electrolyte in the positive and negative electrodes and the diaphragm, thereby helping to reduce concentration polarization during the fast charge cycle. It is preferred to control the mass fractions of lithium salts, film formers, and wetting agents within the above range, which helps to further reduce the impedance of the electrolyte, thereby helping to improve the cycle stability of lithium-ion batteries under fast charge conditions.
[0020] In order to further improve the wetting effect of the electrolyte and thus reduce the impedance of the electrolyte, in one embodiment of the present application, preferably, R1 to R6 are each independently selected from any one of a sulfonate group, hydrogen, a halogen, a substituted or unsubstituted C1 to C6 alkyl group, a substituted or unsubstituted C1 to C6 alkoxy group, a substituted or unsubstituted C3 to C6 cycloalkyl group, a substituted or unsubstituted C2 to C6 alkenyl group, and a substituted or unsubstituted C2 to C6 alkynyl group; and / or, the sulfonate group is selected from any one of a lithium sulfonate group, a sodium sulfonate group, and a potassium sulfonate group.
[0021] In one embodiment of the present application, the wetting agent is selected from any one or more of fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, 1,3,5-trifluorobenzene, 4-methylbenzenesulfonate lithium, sodium p-methylbenzenesulfonate, sodium styrenesulfonate, sodium isopropylbenzenesulfonate, potassium p-toluenesulfonate, potassium p-styrenesulfonate, lithium p-styrenesulfonate, potassium P-fluorobenzenesulfonic acid, lithium p-ethylbenzenesulfonate and sodium pentafluorobenzenesulfonate; preferably, the wetting agent is a combination of 1,3,5-trifluorobenzene and 4-methylbenzenesulfonate lithium, and the mass ratio of 1,3,5-trifluorobenzene to 4-methylbenzenesulfonate lithium is 1:2 to 2.5, and the total mass content of 1,3,5-trifluorobenzene and 4-methylbenzenesulfonate lithium in the electrolyte is 0.8 to 3.5%.
[0022] Fluorobenzene wetting agents have a lower density. Adding them into the electrolyte helps to reduce the density of the electrolyte. From the surface tension calculation formula, it can be seen that the surface tension of the electrolyte is positively correlated with the density. Therefore, when fluorobenzene wetting agents are introduced into the electrolyte, it helps to reduce the surface tension of the electrolyte and improve the wetting rate of the electrolyte in the positive and negative electrode sheets. 1,3,5-trifluorobenzene has a lower density, but its oxidation potential is very forward. When the amount added is large, it is not conducive to reducing the occurrence of its side reactions; lithium 4-methylbenzenesulfonate belongs to the salt substance and can be used as a good surfactant to reduce the surface tension of the electrolyte and improve the wetting performance. At the same time, since lithium 4-methylbenzenesulfonate has better oxidation resistance than 1,3,5-trifluorobenzene, the preferred wetting agent is a combination of 1,3,5-trifluorobenzene and lithium 4-methylbenzenesulfonate, and the mass ratio of 1,3,5-trifluorobenzene and lithium 4-methylbenzenesulfonate is controlled within the above range, which helps to improve the electrolyte wetting performance and also helps to inhibit the side reactions caused by the wetting agent. It is preferred to control the total mass content of 1,3,5-trifluorobenzene and lithium 4-methylbenzenesulfonate in the electrolyte within the above range, which helps to give full play to the mutual synergistic cooperation between the components, thereby helping to further improve the wetting effect and cycle stability of the electrolyte.
[0023] In one embodiment of the present application, the above-mentioned solvent includes a carboxylate solvent; the mass content of the carboxylate solvent in the electrolyte is 5% to 40%; preferably, the mass ratio of the carboxylate solvent to the wetting agent is 10 to 200:1; preferably, the carboxylate solvent is a short-chain linear carboxylate solvent; preferably, the structural formula of the short-chain linear carboxylate solvent is:
[0024] Among them, R7 and R8 are each independently selected from any one of hydrogen, halogen, substituted or unsubstituted C1~C3 alkyl, substituted or unsubstituted C2~C4 alkenyl, substituted or unsubstituted C2~C4 alkynyl, substituted or unsubstituted C1~C4 alkoxy, substituted or unsubstituted C2~C4 alkenyloxy, and substituted or unsubstituted C2~C4 alkynyloxy; preferably, the substituents in R7 and R8 are halogen.
[0025] The addition of carboxylate solvents helps to reduce the overall viscosity of the electrolyte and improve the mobility of lithium ions; at the same time, carboxylate solvents have a low binding energy with lithium ions, which helps to promote rapid desolvation of lithium ions at the interface, thereby helping to reduce lithium deposition and dendrite growth at the anode, and further helping to improve the stability of the battery fast charge cycle. If the content of carboxylate solvents is too high and the content of wetting agent is too low, although the viscosity of the electrolyte can be significantly reduced, the wetting ability of the electrolyte is not only related to the viscosity, but also to the surface tension of the electrolyte. If the content of wetting agent is too low, the viscosity of the electrolyte is at a high value, which is not conducive to improving the fluidity of the electrolyte, and thus is not conducive to the migration of lithium ions; and if the content of wetting agent is too high, side reactions are prone to occur at high temperatures, which is not conducive to fast charge cycles. It is preferred to control the mass ratio of carboxylate solvents to wetting agents within the above range, which helps to improve the synergistic effect between the two, thereby helping to further improve the wetting effect of the electrolyte, thereby helping to reduce the impedance of the electrolyte.
[0026] In order to further reduce the viscosity of the electrolyte and improve the stability of the electrolyte, in one embodiment of the present application, it is preferred that the short-chain linear carboxylic acid ester solvent is ethyl acetate and / or ethyl difluoroacetate.
[0027] In order to further improve the stability of the electrolyte, in one embodiment of the present application, it is preferred that the above-mentioned solvent also includes other solvents, and the other solvents are selected from any one or more of carbonate solvents, cyclic carboxylic acid ester solvents, sulfate solvents, sulfite solvents, anhydride solvents, phosphate solvents, phosphite solvents, amide solvents, nitrile solvents, sulfone solvents and ether solvents; preferably, the other solvent is selected from ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, dipropylene carbonate. Esters, ethyl methyl carbonate, γ-butyrolactone, propionic anhydride, N-methylformamide, N-methylacetamide, acetonitrile, sulfolane, dimethyl sulfoxide, ethylene sulfite, propylene sulfite, triethyl phosphate, methyl ethyl phosphite, methyl sulfide, diethyl sulfite, dimethyl sulfite, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, any one or more of fluorine-containing cyclic organic esters and sulfur-containing cyclic organic esters.
[0028] In one embodiment of the present application, the other solvent is a combination of ethylene carbonate and dimethyl carbonate, and the mass ratio of ethylene carbonate to dimethyl carbonate is 2:7 to 3:1.
[0029] The addition of ethylene carbonate helps to improve the solubility of lithium salts in the electrolyte and promote the formation of SEI film. The viscosity of dimethyl carbonate is relatively low, and its addition helps to reduce the overall viscosity of the electrolyte, thereby helping to increase the migration rate of lithium ions. It is preferred to control the mass ratio of ethylene carbonate and dimethyl carbonate within the above range, which helps to maintain good electrochemical properties of the electrolyte while taking into account the rapid migration of lithium ions and the stable formation of SEI film.
[0030] In one embodiment of the present application, the above-mentioned film-forming agent is selected from any one or more of vinylene carbonate, fluoroethylene carbonate, ethylene carbonate, difluoroethylene carbonate, 1,3-propyl sulfonate, 1,3-propylene sultone, vinyl sulfite, vinyl sulfate, methylene disulfonate, tris(trimethylsilyl)phosphate, 1,2,3-tris(2-cyano)propane, adiponitrile and succinonitrile; preferably, the film-forming agent is selected from any one or more of vinylene carbonate, fluoroethylene carbonate and tris(trimethylsilyl)phosphate; further preferably, the film-forming agent is a combination of vinylene carbonate, fluoroethylene carbonate and tris(trimethylsilyl)phosphate, and the mass ratio of vinylene carbonate, fluoroethylene carbonate and tris(trimethylsilyl)phosphate is 1:4:0.8 to 4:1:1.
[0031] The addition of film formers helps to form a mechanically stable SEI film preferentially at the positive and negative electrodes, and can continuously repair the SEI film, thereby helping to improve the cycle performance of the battery. The addition of vinylene carbonate helps to form an organic component SEI film. The addition of fluoroethylene carbonate introduces fluoride into the SEI film, which helps to improve the flexibility of the SEI film. Tris(trimethylsilyl)phosphate forms a hydrophobic layer in the SEI film through its silane group, which helps to reduce the presence of water molecules, thereby helping to reduce the generation of HF and improve the stability of the SEI film. However, if the content of fluoroethylene carbonate is too high, it is easy to produce hydrogen fluoride at high temperatures, which can easily lead to the dissolution of iron elements in an acidic environment, damage to the positive electrode active material, and serious capacity decay; at the same time, HF will corrode the SEI film, react with alkyl lithium carbonate or Li2CO3 in the SEI film to produce gas and other precipitates, which will lead to a decrease in the stability of the SEI film, which is not conducive to fast charging cycles. Preferably, the mass ratio of vinylene carbonate, fluoroethylene carbonate and tris(trimethylsilyl)phosphate is controlled within the above range, which helps to fully exert the synergistic effect among the three, thereby helping to further improve the stability of the SEI film.
[0032] In order to further improve the mobility of lithium ions, in one embodiment of the present application, the above-mentioned lithium salt is preferably selected from any one or more of lithium hexafluorophosphate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate, lithium tetrafluorooxalatophosphate, lithium difluorobis(oxalatophosphate), lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(pentafluoroethylsulfonyl)imide and tris(trifluoromethylsulfonyl)methyllithium.
[0033] In one embodiment of the present application, the electrolyte includes, by mass percentage: 12.5% of lithium salt, 25% of carboxylic acid ester solvent, 5% of film-forming agent, 56.7% of other solvents, and 0.8% of wetting agent, the lithium salt is lithium hexafluorophosphate, the film-forming agent is a combination of vinylene carbonate and fluoroethylene carbonate, and the mass ratio of vinylene carbonate to fluoroethylene carbonate is 1:4, the carboxylic acid ester solvent is ethyl difluoroacetate, the other solvent is a combination of vinyl carbonate and dimethyl carbonate, and the mass ratio of vinyl carbonate to dimethyl carbonate is 2:7, and the wetting agent is a combination of 1,3,5-trifluorobenzene and lithium 4-methylbenzenesulfonate, and the mass ratio of 1,3,5-trifluorobenzene to lithium 4-methylbenzenesulfonate is 1:2.5.
[0034] In one embodiment of the present application, the electrolyte comprises, by mass percentage: 12.5% of lithium salt, 25% of carboxylic acid ester solvent, 5% of film-forming agent, 54% of other solvents, and 3.5% of wetting agent, the lithium salt is lithium hexafluorophosphate, the film-forming agent is a combination of vinylene carbonate, fluoroethylene carbonate and tris(trimethylsilyl)phosphate, and the mass ratio of vinylene carbonate, fluoroethylene carbonate and tris(trimethylsilyl)phosphate is 4:1:1, the carboxylic acid ester solvent is ethyl difluoroacetate, the other solvent is a combination of vinyl carbonate and dimethyl carbonate, and the mass ratio of vinyl carbonate and dimethyl carbonate is 2:7, the wetting agent is a combination of 1,3,5-trifluorobenzene and lithium 4-methylbenzenesulfonate, and the mass ratio of 1,3,5-trifluorobenzene and lithium 4-methylbenzenesulfonate is 1:2.
[0035] In one embodiment of the present application, the electrolyte comprises, by mass percentage: 12.5% of lithium salt, 25% of carboxylic acid ester solvent, 5% of film-forming agent, 55% of other solvents, and 2.5% of wetting agent, the lithium salt is lithium hexafluorophosphate, the film-forming agent is a combination of vinylene carbonate, fluoroethylene carbonate and tris(trimethylsilyl)phosphate, and the mass ratio of vinylene carbonate, fluoroethylene carbonate and tris(trimethylsilyl)phosphate is 4:1:1, the carboxylic acid ester solvent is ethyl difluoroacetate, the other solvent is a combination of vinyl carbonate and dimethyl carbonate, and the mass ratio of vinyl carbonate and dimethyl carbonate is 2:7, and the wetting agent is lithium 4-methylbenzenesulfonate.
[0036] In another typical embodiment of the present application, a lithium-ion battery is provided, including a positive electrode sheet, an electrolyte and a negative electrode sheet, wherein the electrolyte is the aforementioned electrolyte solution.
[0037] Since the above-mentioned battery contains the electrolyte of the present application, the battery has excellent cycle stability, especially under fast charging conditions, the battery can still maintain excellent cycle stability.
[0038] In order to further improve the cycle stability of the battery, in one embodiment of the present application, the positive electrode active material of the battery is preferably selected from any one or more of LiFePO4, element-doped LiFePO4 and carbon-coated LiFePO4, wherein the doped element is selected from any one or more of Ti, Co, Zn, Mn, La, V and Mg; and / or, the negative electrode active material of the battery is a graphite negative electrode mixed with silicon material, and the mass content of silicon is ≤5%.
[0039] In one embodiment of the present application, the compaction density of the positive electrode of the battery is 1.4-1.66 g / cm 3 ; and / or, the compaction density of the negative electrode of the battery is 2.30 to 2.55 g / cm 3 .
[0040] If the compaction density of the positive and negative electrodes is too low, it is not conducive to reducing the impedance and electrolyte infiltration, and thus is not conducive to the fast charge cycle of the battery. If the compaction density of the positive and negative electrodes is too high, it is not conducive to reducing the risk of crushing the positive and negative electrode materials and reducing the pore impedance of the electrode sheet. It is preferred to control the compaction density of the positive and negative electrodes within the above range, which helps to further improve the fast charge cycle stability of the battery.
[0041] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0042] Example 1
[0043] In an argon atmosphere glove box with a water content of less than 10 ppm, a carboxylate solvent and other solvents are mixed uniformly to obtain an organic solvent, and then a lithium salt, a film-forming agent and a wetting agent are added to the organic solvent and mixed uniformly to obtain an electrolyte, wherein the electrolyte includes 12.5% of a lithium salt, 25% of a carboxylate solvent, 5% of a film-forming agent, 55% of other solvents, and 2.5% of a wetting agent, the lithium salt is lithium hexafluorophosphate, the film-forming agent is a combination of vinylene carbonate and fluoroethylene carbonate, and the mass ratio of vinylene carbonate to fluoroethylene carbonate is 1:4, the carboxylate solvent is ethyl difluoroacetate, the other solvent is a combination of vinyl carbonate and dimethyl carbonate, and the mass ratio of vinyl carbonate to dimethyl carbonate is 2:7, and the wetting agent is lithium 4-methylbenzenesulfonate.
[0044] Example 2
[0045] The difference from Example 1 is that the electrolyte includes 10% lithium salt, 5% carboxylic acid ester solvent, 0.5% film-forming agent, 84.45% other solvents, and 0.05% wetting agent.
[0046] Example 3
[0047] The difference from Example 1 is that the electrolyte includes 18% lithium salt, 40% carboxylic acid ester solvent, 10% film-forming agent, 28% other solvents, and 4% wetting agent.
[0048] Example 4
[0049] The difference from Example 1 is that the wetting agent is 1,3,5-trifluorobenzene.
[0050] Example 5
[0051] The difference from Example 1 is that the wetting agent is a combination of 1,3,5-trifluorobenzene and lithium 4-methylbenzenesulfonate, and the mass ratio of 1,3,5-trifluorobenzene to lithium 4-methylbenzenesulfonate is 1:2, the mass content of the wetting agent is 3.5%, and the mass content of other solvents is 54%.
[0052] Example 6
[0053] The difference from Example 1 is that the wetting agent is a combination of 1,3,5-trifluorobenzene and lithium 4-methylbenzenesulfonate, and the mass ratio of 1,3,5-trifluorobenzene to lithium 4-methylbenzenesulfonate is 1:2.5, the mass content of the wetting agent is 0.8%, and the mass content of other solvents is 56.7%.
[0054] Example 7
[0055] The difference from Example 1 is that the mass fraction of the carboxylate solvent is 27.36%, the mass fraction of the wetting agent is 0.14%, and the mass ratio of the carboxylate solvent to the wetting agent is 195:1.
[0056] Example 8
[0057] The difference from Example 1 is that the mass fraction of the carboxylate solvent is 27.4%, the mass fraction of the wetting agent is 0.1%, and the mass ratio of the carboxylate solvent to the wetting agent is 274:1.
[0058] Example 9
[0059] The difference from Example 1 is that the mass ratio of ethylene carbonate to dimethyl carbonate is 3:1.
[0060] Example 10
[0061] The difference from Example 1 is that the mass ratio of ethylene carbonate to dimethyl carbonate is 4:1.
[0062] Embodiment 11
[0063] The difference from Example 1 is that the film former is a combination of vinylene carbonate, fluoroethylene carbonate and tris(trimethylsilyl)phosphate, and the mass ratio of vinylene carbonate, fluoroethylene carbonate and tris(trimethylsilyl)phosphate is 1:4:0.8.
[0064] Example 12
[0065] The difference from Example 1 is that the film former is a combination of vinylene carbonate, fluoroethylene carbonate and tris(trimethylsilyl)phosphate, and the mass ratio of vinylene carbonate, fluoroethylene carbonate and tris(trimethylsilyl)phosphate is 4:1:1.
[0066] Comparative Example 1
[0067] The difference from Example 1 is that the electrolyte includes 12.5% of lithium salt, 25% of carboxylic acid ester solvent, 5% of film-forming agent, 10% of wetting agent, and 47.5% of other solvents.
[0068] Comparative Example 2
[0069] The difference from Example 1 is that the electrolyte includes 12.5% of lithium salt, 25% of carboxylic acid ester solvent, 5% of film-forming agent, and 57.5% of other solvents.
[0070] Preparation of positive electrode sheet: The lithium iron phosphate positive electrode active material is mixed with the conductive agent multi-walled carbon nanotube, the conductive agent single-walled carbon nanotube, and the binder polytetrafluoroethylene in a mass ratio of 98:0.55:0.45:1, and then the solvent N-methylpyrrolidone is added thereto, and the system is stirred under the action of a vacuum mixer until it becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet; the compaction density of the positive electrode sheet is 2.44g / cm 3 .
[0071] Preparation of negative electrode sheet: Mix the negative electrode active material, sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 96:2:2, add deionized water, and prepare a slurry with a solid content of 45wt%, and stir evenly to obtain a negative electrode slurry. Among them, the negative electrode active material is a mixture of graphite and silicon-based material SiO in a mass ratio of 90:10. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 10μm, and dried at 120°C to obtain a negative electrode sheet coated with a negative electrode material layer on one side. Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides. After cold pressing and slitting, the negative electrode sheet is obtained for standby use, wherein the compaction density of the negative electrode sheet is 1.55g / cm 3 .
[0072] Battery preparation: A 10 μm polypropylene porous film is used as a separator. The positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play a role of isolation, and then wound into an electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag, baked at 80°C to remove water, and then injected with the electrolyte prepared in the embodiment and comparative example. After vacuum packaging, standing, formation, shaping and other processes, the preparation of the lithium-ion battery is completed.
[0073] Performance Testing
[0074] The prepared lithium-ion battery was charged to 3.65V at 3C constant current at 25°C, left for 30 minutes, and then discharged to 2.5V at 0.5C constant current. The discharge capacity was recorded as the first discharge capacity. The above charge and discharge cycle was repeated 500 times, and the discharge capacity of the 300th cycle was recorded. 3C cycle capacity retention rate (%) = 300th cycle discharge capacity / first discharge capacity × 100%. The test results are shown in Table 1.
[0075] Table 1
[0076]
[0077] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0078] The appropriate addition of lithium salt in this application helps to improve the transmission efficiency of lithium ions. The appropriate addition of film-forming agent helps to form a stable SEI film on the surface of the positive and negative electrodes. The presence of SEI film helps to protect the electrode material from corrosion by the electrolyte, thereby helping to reduce the occurrence of side reactions, especially under high temperature or high rate charge and discharge conditions. The continuously repaired SEI film can effectively inhibit further reaction between the interface and the electrolyte, thereby helping to improve the cycle stability and safety of the battery. The addition of wetting agent helps to reduce the surface tension of the electrolyte, thereby facilitating the rapid penetration of the electrolyte in the electrode and the diaphragm, especially at high rate charge and discharge, which helps to reduce the desolvation energy of lithium ions on the electrode surface and reduce lithium deposition and dendrite formation. The wetting agent of the present application is an additive of a benzene structure. By introducing a halogen or sulfonate group on the benzene ring, it helps to achieve the hydrophilic and lipophilic properties of the wetting agent, and acts as a surfactant component in the electrolyte. The main structure of benzene is lipophilic, and the substituent is hydrophilic, which helps to rapidly reduce the surface tension of the electrolyte and improve the wetting effect of the electrolyte in the positive and negative electrodes and the diaphragm, thereby helping to reduce concentration polarization during the fast charge cycle. It is preferred to control the mass fractions of lithium salts, film formers, and wetting agents within the above range, which helps to further reduce the impedance of the electrolyte, thereby helping to improve the cycle stability of lithium-ion batteries under fast charge conditions.
[0079] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An electrolyte, characterized in that: In terms of mass percentage, the electrolyte comprises: 10% to 18% lithium salt; 0.5% to 10% film-forming agent; 0.05% to 5% of a wetting agent; and The remaining amount of solvent; The structural formula of the infiltrant is: wherein R1 to R6 are independently selected from sulfonate, hydrogen, halogen, substituted or unsubstituted C1 to C 10 Alkyl, substituted or unsubstituted C1~C 10 Alkoxy, substituted or unsubstituted C3~C 10 Cycloalkyl, substituted or unsubstituted C2~C 10 Alkenyl, substituted or unsubstituted C2~C 10 Any one of alkynyl groups, and at least one substituent among R1 to R6 is a halogen or sulfonate group.
2. The electrolyte according to claim 1, characterized in that The R1-R6 are each independently selected from any one of sulfonate group, hydrogen, halogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C1-C6 alkoxy, substituted or unsubstituted C3-C6 cycloalkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl; And / or, the sulfonate group is selected from any one of a lithium sulfonate group, a sodium sulfonate group, and a potassium sulfonate group.
3. The electrolyte according to claim 2, characterized in that The infiltrant is selected from any one or more of fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, 1,3,5-trifluorobenzene, 4-methylbenzenesulfonate lithium, sodium p-methylbenzenesulfonate, sodium styrenesulfonate, sodium isopropylbenzenesulfonate, potassium p-toluenesulfonate, potassium p-styrenesulfonate, lithium p-styrenesulfonate, potassium P-fluorobenzenesulfonic acid, lithium p-ethylbenzenesulfonate and sodium pentafluorobenzenesulfonate; Preferably, the wetting agent is a combination of 1,3,5-trifluorobenzene and lithium 4-methylbenzenesulfonate, and the mass ratio of the 1,3,5-trifluorobenzene to the lithium 4-methylbenzenesulfonate is 1:2-2.5, and the total mass content of the 1,3,5-trifluorobenzene and the lithium 4-methylbenzenesulfonate in the electrolyte is 0.8-3.5%.
4. The electrolyte according to any one of claims 1 to 3, characterized in that The solvent includes a carboxylic acid ester solvent; the mass content of the carboxylic acid ester solvent in the electrolyte is 5% to 40%; Preferably, the mass ratio of the carboxylic acid ester solvent to the wetting agent is 10 to 200:1; Preferably, the carboxylate solvent is a short-chain linear carboxylate solvent; Preferably, the structural formula of the short-chain linear carboxylic acid ester solvent is: Wherein, R7 and R8 are each independently selected from any one of hydrogen, halogen, substituted or unsubstituted C1~C3 alkyl, substituted or unsubstituted C2~C4 alkenyl, substituted or unsubstituted C2~C4 alkynyl, substituted or unsubstituted C1~C4 alkoxy, substituted or unsubstituted C2~C4 alkenyloxy, substituted or unsubstituted C2~C4 alkynyloxy; preferably, the substituents in R7 and R8 are halogen.
5. The electrolyte according to claim 4, characterized in that The short-chain linear carboxylic acid ester solvent is ethyl acetate and / or ethyl difluoroacetate.
6. The electrolyte according to any one of claims 1 to 5, characterized in that The solvent further comprises other solvents, and the other solvents are selected from any one or more of carbonate solvents, cyclic carboxylic acid ester solvents, sulfate solvents, sulfite solvents, anhydride solvents, phosphate solvents, phosphite solvents, amide solvents, nitrile solvents, sulfone solvents and ether solvents; Preferably, the other solvent is selected from any one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, γ-butyrolactone, propionic anhydride, N-methylformamide, N-methylacetamide, acetonitrile, sulfolane, dimethyl sulfoxide, ethylene sulfite, propylene sulfite, triethyl phosphate, methyl ethyl phosphite, methyl sulfide, diethyl sulfite, dimethyl sulfite, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, fluorine-containing cyclic organic esters and sulfur-containing cyclic organic esters.
7. The electrolyte according to claim 6, characterized in that The other solvent is a combination of ethylene carbonate and dimethyl carbonate, and the mass ratio of the ethylene carbonate to the dimethyl carbonate is 2:7 to 3:
1.
8. The electrolyte according to any one of claims 1 to 7, characterized in that The film-forming agent is selected from any one or more of vinylene carbonate, fluoroethylene carbonate, ethylene carbonate, difluoroethylene carbonate, 1,3-propyl sulfonate, 1,3-propylene sultone, vinyl sulfite, vinyl sulfate, methylene disulfonate, tris(trimethylsilyl)phosphate, 1,2,3-tris(2-cyano)propane, adiponitrile and succinonitrile; Preferably, the film-forming agent is selected from any one or more of vinylene carbonate, fluoroethylene carbonate and tris(trimethylsilyl)phosphate; It is further preferred that the film-forming agent is a combination of vinylene carbonate, fluoroethylene carbonate and tris(trimethylsilyl)phosphate, and the mass ratio of the vinylene carbonate, the fluoroethylene carbonate and the tris(trimethylsilyl)phosphate is 1:4:0.8 to 4:1:
1.
9. The electrolyte according to any one of claims 1 to 8, characterized in that The lithium salt is selected from any one or more of lithium hexafluorophosphate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate, lithium tetrafluorooxalatophosphate, lithium difluorobis(oxalatophosphate), lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(pentafluoroethylsulfonyl)imide and tris(trifluoromethylsulfonyl)methyllithium.
10. A lithium ion battery comprising a positive electrode, an electrolyte and a negative electrode, characterized in that: The electrolyte is the electrolytic solution according to any one of claims 1 to 9.
Citation Information
Cited By
Lithium ion battery and electric device
CN120319872A
Lithium ion battery
CN121307153A